Повышение эффективности действия депрессорных присадок добавлением нефтяных смол - Шафер С. Е. Савелий Егорович; Титаева А. М. Алина Маратовна; Ефанова А. О. Альвина Олеговна; Морозова Я. П. Яна Павловна; Киргина М. В. Мария Владимировна (2023, 2023)
Заглавие с экрана